Project management beyond Waterfall and Agile - Ajam, Mounir A. (Best practices and advances in program management series., 2018)
"The book presents a flexible, universal, and integrated three-dimensional model for managing projects. By tailoring and customizing the model to a specific industry or organization or by adapting it to a function or project classification, this model can be used to manage any project. It can also be used both in a traditional or an agile environment. The model's three dimensions are project lifecycle, project management processes, and finally competences, sustainability, and best practices. The book explains how these dimensions are managed together and how to apply and adapt the three-dimensional model."--Provided by publisher.